The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017 IEEE Globecom Workshops (GC Wkshps) 2017
DOI: 10.1109/glocomw.2017.8269123
|View full text |Cite
|
Sign up to set email alerts
|

Secure Full-Duplex Device-to-Device Communication

Abstract: This paper considers full-duplex (FD) device-todevice (D2D) communications in a downlink MISO cellular system in the presence of multiple eavesdroppers. The D2D pair communicate sharing the same frequency band allocated to the cellular users (CUs). Since the D2D users share the same frequency as the CUs, both the base station (BS) and D2D transmissions interfere each other. In addition, due to limited processing capability, D2D users are susceptible to external attacks. Our aim is to design optimal beamforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Meanwhile, it also shows that the secure coverage probabilities for both users will decrease as β increases. Furthermore, from (9) and (13), it is shown that the CU's secure coverage probability is only relate to the relative position with UAV and their eavesdroppers, and the scope of communication area. While the secure coverage of DUs are affected by many parameters, as the impact of 0 Fig.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, it also shows that the secure coverage probabilities for both users will decrease as β increases. Furthermore, from (9) and (13), it is shown that the CU's secure coverage probability is only relate to the relative position with UAV and their eavesdroppers, and the scope of communication area. While the secure coverage of DUs are affected by many parameters, as the impact of 0 Fig.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Under the circular-shaped UAV secure coverage, the formula (9) and (13) have shown that the CU's secure coverage probability is a function of both h and C R (but not of U P ). In this case, the mobile UAV is capable of both providing secure communication enhancement with variant h values and serving area after performing parameter adjustment.…”
Section: The Benefits Brought About By Employing Mobile Uavmentioning
confidence: 99%
See 2 more Smart Citations
“…These mechanisms take into account the locations of homogeneous spatial Poisson point processes for FD-D2D users. Moreover, there are other promising techniques being considered that coexist with FD-D2D, such as FD-D2D underlying cellular networks equipped with base station MIMO antennas, as explored in [20,21]. However, the previous studies typically concentrate on overall cell performance improvement, with only a limited number of works focusing on maximizing D2D link throughput, as discussed in [19].…”
Section: Introductionmentioning
confidence: 99%